PENGARUH INVESTASI PT AQUAFARM NUSANTARA TERHADAP PERTUMBUHAN EKONOMI SUMATERA UTARA (2008-2010) - Pandiangan, Oktavianus; Rani, Faisyal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study is an elaborate study of the Influence of Investment PT Aquafarm Nusantara for North Sumatera Economic Growth (2008-2010). The purpose of this study was to clarify the effect of foreign investment on economic growth in North Sumatera . According to Krugman is the Capital of Foreign Direct Investment is the flow of international capital from a country where companies establish or expand his company in another country. PT Aquafarm Nusantara is a multinational company from Switzerland engaged in the fisheries sector. PT Aquafarm has expanded its business in Indonesia since 1988 and decided to expand its business to North Sumatra since 1998.This research was developed based on the framework of neoliberalism perspective that is supported by the theory of foreign direct investment, as well as the level of analysis using multinational coorporationi as the main actor in international relations. The concept leads to qualitative methods and the study of literature as a source of information.The results of this study found investment by PT Aquafarm Nusantara to influence several sectors of economic growth in North Sumatra, among others, the development of investment value in the fisheries sector, increasing North Sumatra's economic growth by increasing foreign investment, reducing unemployment, reducing poorness in North Sumatra. From these result, it can mean that direct foreign investment provides benefits to the economy growth to the communities in North Sumatera both locally and to the goverment of Indonesia.Keywords: Effect, Foreign Direct Investment, Economy Growth, PT Aquafarm Nusantara, North Sumatera